Balancing international public goods and accountability: Exploring the impact of IFPRI’s policy research on science, technology, and innovation - Lynam, John K. (International Food Policy Research Institute, 2016)
As the two case studies suggest, STI impact is highly context-specific, and must often adapt to a changing decision-making milieu. Partner engagement is a critical piece in moving policy research to outcomes, as is reflected in IFPRI’s most recent strategy and increased deployment of personnel to country programs. However, local deployment for impact comes at the expense of critical mass at headquarters and the ability to engage in emerging trends in scientific discovery. And, as the review highlights, such critical mass can only be deployed over a limited number of research themes. As the IFPRI STI team explores the next strategic focus for its research, it faces the difficult question of how to balance the increasing emphasis on accountability, and therefore impact, with the ability of IFPRI to define new research areas and generate IPGs in this critical policy area.